Upper Cretaceous foraminifera and palynomorphs from Ekelöf coast Section, Ekelöf Point, Eastern James Ross Island, Antarctic Peninsula - Carames, Andrea Alejandra (2016)
A micropaleontological analysis of foraminifera and palynomorphs obtained from a partial sedimentary section cropping out at Ekelöf Point, eastern James Ross Island, Antarctic Peninsula, is presented. The section, named Ekelöf Coast, includes the lowest levels of the Upper Cretaceous Hamilton Point Member of the Snow Hill Island Formation. Among the foraminifera, 18 benthictaxa including 10 agglutinated and eight calcareous are recognized. Palynomorphs include continental and marine species. The continental assemblage contains 44 spore and pollen species. The marine assemblage consists of 10 peridinioid dinoflagellate cysts species, dominating in number of specimens, and 10 gonyaulacoids. Although the palynomorph assemblage supports a late Campanian age for the section, an earliest Maastrichtian age is not excluded. The paleoenvironmental interpretation based on the distribution of foraminiferal morphogroups indicates an outer shelf-upper bathyal environment in agreement with sedimentological data. The paleoenvironmental inference based on the S/D ratio (sporomorph versus din of lagellate cysts) and the P/G ratio (pendinioid versus gonyaulacoid cysts) suggest a coastal to inner neritic setting with a continuous continental supply from the continent to the marine environment, evidenced by the slight dominance of the peridionoids over gonyaulacoids cysts. The discrepancy observed between palynological and micropaleontological-sedimentological data may be linked to the development of a narrow continental shelf during the Late Cretaceous. In such continental shelf, terrestrial palynomorphs and peridinoid cysts would quickly run down the slope and would be deposited in the deep marine environment together with gonyaulacoid cysts.